The influence of dynamic and plyometric exercises on knee joint motion for countermovement jump performance - Campana Bonilla, M. V.; Alsowayan, M. N. (ISBS Proceedings Archive (Michigan), 2020)
This study aims to analyse the effects of dynamic and plyometric exercises on knee joint motion for countermovement jump (CMJ) performance. The CMJ test was performed on 45 college male non-athletes who were categorised into three groups; a dynamic group (DG) performing dynamic exercises, a plyometric group (PG) performing jumping exercises, a control group (EG) performing traditional exercises for physical education. Motion analysis data from the knee joint angles were obtained during countermovements in the sagittal plane using video recording. The results showed that plyometric and dynamic exercises could improve jumping performance in college non-athletes and enhance the strength, force, and power of lower limb muscles and joints. Furthermore, the motion analysis helped identify a range of motions in knee joints, dynamic, and plyometric exercises that contribute to jumping performance.